Factors Related to Postpartum Mothers Knowledge of Exclusive Breastfeeding in the Tuntungan Health Center Work Area, Pancur Batu Subdistrict - Edy Marjuang Purba; Anna Waris Nainggolan; Saut Purba (Lembaga Pengembangan Kinerja Dosen, 2025)
The 2023 Indonesian Health Survey stated that the proportion of exclusive breastfeeding in Sumatera Utara Province was quite low, namely 43.9%. The low coverage of exclusive breastfeeding is closely related to the lack of knowledge of postpartum mothers, which is a predisposing factor that encourages mothers to only give breast milk for 6 months to their babies. The purpose of this study was to determine the factors related to postpartum mothers' knowledge of exclusive breastfeeding in the Tuntungan Health Center work area, Pancur Batu Subdistrict. This study was an observational analytic study with a cross-sectional design. The sample in the study were postpartum mothers in the Tuntungan Health Center work area who met the inclusion and exclusion criteria, namely 50 people. The data collected were primary data obtained through questionnaires distributed to postpartum mothers. Bivariate analysis was carried out using the chi-square test to determine the relationship between the independent and dependent variables. Based on the study conducted, it is known that there is a relationship between age (p-value = 0.015), education (p-value = 0.026), and parity (p-value = 0.008) with postpartum mothers' knowledge of exclusive breastfeeding. There is no relationship between occupation (p-value = 0.224) and postpartum mothers' knowledge of exclusive breastfeeding. It is recommended that health workers in the Tuntungan Health Center work area, Pancur Batu Subdistrict, to improve the knowledge of postpartum mothers, especially for young mothers (<20 years) and primigravida mothers. It is also recommended that postpartum mothers improve their knowledge through various media, especially social media.